(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This insightful article delves into the intricate world of syntax, elucidating its fundamental units and dissecting two contrasting yet complementary approaches: the traditional and cognitive perspectives. The exposition meticulously unfolds the main units of syntax—words, phrases, clauses, and sentences—providing a comprehensive overview of their roles in shaping linguistic structures.